ANALISIS MODAL KERJA PADA KOPERASI KARYAWAN PT. BANK SULUT DI MANADO - RUNTURAMBI, EKA Y.A; TAMPI, JOHNY. REVO. E; Runtuwene, R. (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
ABSTRACT Good working capital management determine the success of a company. Assessment of working capital have led to the liquidity ratio; Current ratio, Quick ratio, cash ratio, and the ratio of the activity; Working Capital Turnover. The purpose of this study was to determine the management of working capital in the Cooperative Employees PT. Bank of North Sulawesi.The method used is descriptive method using a quantitative approach to the analysis of financial statements. Data and data sources are annual financial statements of the Cooperative Employees PT. Bank of North Sulawesi 2014-2015 fiscal year. Keywords: Working capital management, liquidity, Working capital turnover